Emergency Medical Services response levels and subsequent emergency contacts among patients with a history of mental illness in Denmark: a nationwide study. (October 2021) - Mackenhauer, Julie; Valentin, Jan Brink; Mikkelsen, Søren; Steinmetz, Jacob; Væggemose, Ulla; Christensen, Helle Collatz; Mainz, Jan; Johnsen, Søren Paaske; Christensen, Erika Frischknecht
Abstract : Background and importance: People with mental illness have higher use of emergency services than the general population and may experience problems with navigating in complex healthcare systems. Poor physical health contributes to the excess mortality among the mentally ill. Objective: To compare the level of Emergency Medical Services (EMS) response and subsequent contacts emergency between patients with and without a history of mental illness. Design, setting, and participants: A nationwide cohort study was conducted in Denmark including medical 1-1-2 calls 2016 2017. The healthcare system is financed through taxation allowing free access to healthcare services including ambulance services. Exposure: Exposed groups had a history of major, moderate, or minor mental illness. Outcome measures and analysis: We studied seven national prehospital care Performance Indicators (PI 1–7). The selected PI concerned EMS response levels and subsequent contacts to prehospital and in-hospital services. Exposed groups were compared to nonexposed groups using regression analyses. Results: We included 492 388 medical 1-1-2 calls: 8, 10, and 18% of calls concerned patients with a history of major, moderate, or minor mental illness, respectively. There were no clinically relevant differences regarding response times (PI 1–2) or registration of symptoms (PI 3) between groups. If only telephone advice was offered, patients with a history of major, moderate or minor mental illness were more likely to recall within 24 h (PI 4): adjusted risk ratio (RR) 2.11 (1.88–2.40), 1.96 (1.20–2.21), and 1.38 (1.20–1.60), but less or equally likely to have an unplanned hospital contact within 7 days (PI 6): adjusted RRs 1.05 (0.99–1.12), 1.04 (0.99–1.10), and 0.90 (0.85–0.94), respectively. If released at the scene, the risk of recalling (PI 5) or having an unplanned hospital contact (PI 7) was higher among patients with a history of mental illness: adjusted RRs 2.86 (2.44–3.36), 2.41 (2.05–2.83), and 1.57 (1.35–1.84), and adjusted RRs 2.10 (1.94–2.28), 1.68 (1.55–1.81), and 1.25 (1.17–1.33), respectively. Patients with a history of mental illness were more likely to receive telephone advice only adjusted RRs 1.61 (1.53–1.70), 1.30 (1.24–1.37), and 1.08 (1.04–1.13), and being released at scene adjusted RRs 1.11 (1.08–1.13), 1.03 (1.01–1.04), and 1.05 (1.03–1.07). Conclusion: More than one-third of the study population had a history of mental illness. These patients received a significantly lighter EMS response than patients with no history of mental illness. They were significantly more likely to use the emergency care system again if released at scene. This risk increased with the increasing severity of the mental illness. Abstract : Supplemental Digital Content is available in the text.